Anti-Women Misinformation on YouTube - Mahmud, Md. Rifat; Reza, Raiyan Bin (Universitas Pendidikan Nasional, 2024)
YouTube has faced criticism for facilitating the spread of misinformation targeting women. This study analyzes anti-women content on YouTube to understand the types, volume, and potential harms of misinformation campaigns. Through a content analysis of videos, channels, and discussions networks, we identified common anti-women tropes including claims about feminism, gender politics, relationships, and women - men relationship. The sample of this study (N=100) was drawn from popular videos matching relevant keywords. Videos were coded for message framing. Results show an availability of wide range videos spreading anti women videos. Most of these videos are dominated by male speakers. This study provides empirical evidence that YouTube is a vector for organized misinformation targeting women, with concerning real-world implications. It is imperative for this platform to curb harmful anti-women propaganda using content moderation and algorithm governance.